Historical Evolution of Placemaking in Historic City of Palembang, Indonesia - Muhammad Fajri Romdhoni (International Journal of Built Environment and Scientific Research, 2020)
Because of the rapid transformation of Southeast Asian cities with modernization and westernization, this paper aims to present the historical evolution of Palembang's city into clear morphological phases of the city. Palembang is essential because it represents one of the earliest and historical cities in Southeast Asia and could serve as a good case study to the morphological changes in Southeast Asia. Studies selected for this paper are historical maps on the 17th century, a combination and sets of the early 19th century, and post Indonesia's independence maps that include the latest map of the modern Palembang city. A framework of the historical and interpretive study was conducted and implementing the maps using GIS and OSM as the newest data source and analysis. Using Placemaking theory and utilizing Street pattern, Land use, and landmark as an approach tool to clarify the city's spatial form. Analysis of street patterns, land use, and landmarks was carried out on the three different morphological phases, and we founded out that there have been changes in the quality of place over time. The city form has shifted more complex from a linear settlement and transform into a co-centric form city and later on morphed into a multiple-centered metropolis. The land use had also changed over time due to political, economic conditions, and dwelling pattern. Palembang city's landmarks have also evolved or multiplied over time, and it has given the evolution of meaning to the city. From the changes in the quality of place and geographical model transformations, future studies will need to focus on increasing the quality of place by classifying the city's spatial configuration from its integration, betweenness, and choice that could define the city's network and systems. Future studies will also need to compare the research findings with other cities in the Southeast Asia regions with similar conditions to create a comparison between the results and a better understanding of Historic Southeast Asian cities.